Grammatical devices of stance in written academic English - Sharif Alghazo (Elsevier, 2021)
Stance is a feature of academic writing that refers to how writers interact and engage with their readers by means of linguistic devices. This study focuses on the grammatical devices—and semantic distinctions thereof—that are employed by academic writers of English to express stance in research article abstracts in the areas of applied linguistics (AL) and literature (L). To this end, a corpus of 120 research article abstracts (60 in the area of AL and another 60 in that of L) was built and analysed using SPSS and following Biber et al.’s (1999) framework of grammatical devices of stance. The abstracts were extracted from high-quality journals in the respective areas: Applied Linguistics and English: Journal of the English Association. Both are ISI journals and published by Oxford Academic Publishing. A mixed-method approach, applying quantitative and qualitative measures, was adopted to answer the two questions: How is stance grammatically expressed in AL research article abstracts and L research article abstracts, and How is the expression of stance in AL research article abstracts similar to/different from that in L ones? The findings are construed in light of theories of academic discourse and English for Academic Purposes (EAP). The results reveal that there are important similarities and differences in the extent to which and the means through which stance is expressed in AL research article abstracts and L research article abstracts. In particular, the findings show that both AL and L abstracts were similar in the most frequently used stance marker which is the stance complement clause. However, they were different in the frequency of use of other devices. The study provides insights into the ways academic writers express stance in various fields which better our ability to write research article abstracts.